Two-Stage Operations in Patients with Acute Right-sided Colonic Obstruction: a 15-year Single Institution Experience - Tsai, Nien-Ying; Yu, Chun-Wei; Hsiao, Cheng-Wen; Jao, Shu-Wen; Lo, Cheng-Hsiang; Yang, Chih-Wei; Cheng, Yi-Chiao (Journal of Medical Science, 2023)
ObjectiveThe aim of the study was to review the characteristics, surgical outcomes, complications, and long-term outcomes of two-stage operations for acute right-sided colonic obstruction (RSCO) in a single institution.Summary background dataAlthough patients with acute RSCO can be treated by resection of the tumor with a primary anastomosis, longer procedure times and bigger wounds can result in more mortality and complications. A two-stage operation by diverting loop ileostomy was another surgical option. However, the outcomes of two-stage operations are lacking.Methods           The retrospective study reviewed the patients who underwent emergency surgery for acute RSCO in a tertiary center from 2004-2018. First-stage operations other than diverting loop ileostomy, incomplete obstructions that could be treated medically, or pathologies other than adenocarcinomas were excluded. Perioperative data such as first and second operations, operative times, lengths of stay, harvested lymph nodes, and any complications were included. We assessed overall survival (OS) and disease-free survival (DFS) for the oncologic outcomes.ResultsSixty-nine patients were included. Seven patients had surgical complications related to ileostomy. Three of them died within 30 days of first admission. Thirty-one patients received a second-stage operation by right hemicolectomy. None had anastomosis leakage or 30-day mortality. Only 9.7% of patients had fewer than 12 harvested lymph nodes. One-year OS was 34% in the patients who received only ileostomy, and 89% in those who received two-stage operations (P < 0.001). Among 26 patients who underwent curative resection of tumor, 3-year DFS was 61.5%.ConclusionsA two-stage operation is associated with low mortality and morbidity rates in an emergency setting. The subsequent right hemicolectomy can harvest more lymph nodes than emergency resection. Long-term survival benefits can be expected.